Optimization of Various Flavors of Cashew Nut Processing to Increase The Sales Value of Cashew Nut in Krandegan, Sidorejo, Jatisrono, Wonogiri - Rochmawati Solikhah Sukemi; Suprihatin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Cashew nuts are one of the leading commodities in Krandegan Hamlet, Sidorejo, Wonogiri. Some people sell cashew nuts in raw form for Rp. 115,000,-/kg. Farmers also still use the traditional method of marketing cashew products, namely selling them to the market. This causes many other expenses such as transportation and consumption when selling garden products. This service uses the Asset Based Communities Development (ABCD) method. Assistance to cashew farmers is provided by providing training in making processed cashew nuts. The results of the service showed an increase in the price of cashew nuts after being processed with various flavors. Optimizing the processing of various flavors of cashew nuts can increase the selling value of cashew nuts in Krandegan, Sidorejo, Jatisrono, Wonogiri. Farmers have also started marketing cashew nuts through digital marketing.